KERAGAAN MUTU BIJI KAKAO KERING DAN PRODUK SETENGAH JADI COKELAT PADA BERBAGAI TINGKATAN FERMENTASI - Dian Adi A. Elisabeth; Ludivica Endang Setijorini (LPPM Universitas Terbuka, 2009)
Basic of cocoa bean preparation process is fermentation. Fermentation is done especially to improve and build specific chocolate flavour of cocoa bean and its products, i. e. cocoa liquor, butter, and powder; and also to decrease the disliked flavors, like bitter and acid. Research of cocoa bean fermentation was hold on in Subak Abian Pucaksari, Tabanan. This research involved 20 cooperative farmers with 0,5 hectare farm area per each farmer. The treatment used was time of cocoa bean fermentation, i.e. without fermentation, not fully fermentation (4 days), and fully fermentation (5 days). Variables observed were dried cocoa beans physic and chemical quality, and also cocoa products chemical and organoleptic quality. Organoleptic test done to cocoa liquor and powder was descriptive and ranking test used 15 semi-trained panelists. The result showed that the fermentation process had significant influence to dried cocoa beans chemical quality and its products. Fermentation had no significant influence to dried cocoa beans physic quality. For organoleptic quality attributes, all panelists gave the highest rank for cocoa liquor and powder prepared from fully fermented cocoa bean.